China, Europe, and the Great Divergence: a study in historical national accounting, 980-1850 - Broadberry, S; Guan, H; Li, D (Cambridge University Press, 2018)
As a result of recent advances in historical national accounting, estimates of GDP per capita are now available for a number of European economies back to the medieval period, including Britain, the Netherlands, Italy, and Spain. The approach has also been extended to Asian economies, including India and Japan. So far, however, China, which has been at the center of the Great Divergence debate, has been absent from this approach. This article adds China to the picture, showing that the Great Divergence began earlier than originally suggested by the California School, but later than implied by older Eurocentric writers.